الضبط الذاتي في ضوء بعض المتغيرات الديموجرافية لدى طلبة الجامعة - منصور، هاني نعيم عبدالنور Mansour, Hani Naim Abdulnour; بدوي، نورة محمد طه Badawi, Nourah Mohammed Taha; صادق، مروة صادق أحمد (جامعة الفيوم - كلية التربية, 2022)
هدف البحث إلى التعرف على الفروق في مستوى الضبط الذاتي وأبعاده وفقا للمتغيرات الديموجرافية النوع (ذكور/ إناث)، التخصص الجامعي (أدبي/ علمي)، مكان السكن (ريف/ حضر) لدى طلاب الجامعة، وتكونت عينة البحث من (396) طالب وطالبة منهم (165) طالبا و(231) طالبة ببعض الكليات من طلاب جامعة الفيوم للعام الدراسي (2021/ 2022م)، وقد تراوحت أعمارهم من (18- 22) عاما واعتمد البحث على المنهج الوصفي: واستخدم الباحث مقياس الضبط الذاتي (إعداد الباحث). وقد كشفت نتائج البحث الحالي عن عدم وجود فروق تبعا للنوع في الدرجة الكلية للضبط الذاتي وبعدي التروي وتقييم الذات، في حين أسفرت النتائج عن وجود فروق بين متوسطي درجات الذكور والإناث في بعد إدارة الانفعالات لصالح الذكور، وفي بعد تعزيز الذات لصالح الإناث، كما أسفرت النتائج عن عدم وجود فروق في الضبط الذاتي لدى عينة الدراسة تبعا للتخصص (علمي/ أدبي)، كما كشفت النتائج عن عدم وجود فروق في الضبط الذاتي لدى عينة الدراسة تبعا لمكان السكن (ريف/ حضر). The aim of the research is to identify the differences in the level of self-control and its demographic dimensions, gender (male / female), the university specialization (scientific / literary), place of residence (rural / urban) among University Students, and the research sample consisted of (396) male and female students including (165) male and (231) female students in some faculties of Fayoum University students for the academic year (2021 / 2022), and their ages ranged from (18 / 22) years. The research relied on the descriptive method: correlational, comparative, and the researcher used the self- control scale (prepared by the researcher). The results of research revealed that there were no differences according to gender in the total degree of self- control and the dimensions of perseverance and self- evaluation, while the results revealed that there were differences between the average degrees of males and females in dimension of managing emotions in favor of males, in the domination of self- enhancement in favor of females, the results also revealed that there were no differences in self- control among the study sample according to specialization(scientific / literary), and the results revealed that there were no differences in self- control among the study sample according to the place of residence(rural / urban).
Keywords: طلبة المرحلة الجامعية -- التحكم شعوريا -- الخبرات الحياتية -- الخصائص السيكومترية -- النوع الاجتماعي -- الإرشاد النفسي